Thermoregulation Impairment (Saba CCC) In: Essentials of Nursing Informatics (Appendix) - Saba VK (Thermoregulation Impairment (Saba CCC) In: Essentials of Nursing Informatics (Appendix), 2012)
SCOPE NOTE: Fluctuation of temperature between hypothermia and hyperthermia. Use only as a specific Saba CCC Nursing Diagnosis. Copyright (c) 2012, Virginia K. Saba. CINAHL EDITORIAL SEARCH SUGGESTION: The term THERMOREGULATION IMPAIRMENT (SABA CCC) is used for indexing when articles specifically concern the term or research about the term. For citations that concern the general topic or topics related to the term, consider searching the subject heading: BODY TEMPERATURE REGULATION.